Learning the Qur'an Hadith in Islamic Religious Education as an Effort to Strengthen the Religious Character of Grade IV Students of SD Negeri Jangkang I Tiris Probolinggo - Muhammad Hasan; Endah Tri Wisudaningsih (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
This study aims to analyze the implementation of Qur'an Hadith learning in the subject of Islamic Religious Education as an effort to strengthen the religious character of grade IV students of SD Negeri Jangkang I Tiris Probolinggo. This study uses a qualitative approach with a descriptive research type to gain an in-depth understanding of the learning process and its impact on students' religious character. Data collection techniques were carried out through direct observation of learning activities, semi-structured interviews with school principals, Islamic Religious Education teachers, and grade IV students, as well as documentation of learning activities. Data analysis is carried out qualitatively through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that learning the Qur'an Hadith is carried out in a structured manner through reading, memorizing, understanding the meaning of verses and hadiths, and relating them to students' daily lives. This learning plays an important role in strengthening students' religious character, especially in forming an attitude of faith, discipline in worship, honesty, responsibility, and mutual respect. Supporting factors include teacher competence, school support, and student enthusiasm, while inhibiting factors are limited learning time and differences in students' religious backgrounds. Overall, the learning of the Qur'an Hadith makes a positive contribution to strengthening the religious character of students.